2016
DOI: 10.1080/10428194.2016.1228927
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylating agent combination strategies in myelodysplastic syndromes: hopes and shortcomings

Abstract: The hypomethylating agents (HMA) azacitidine and decitabine are both approved by the FDA for the treatment of myelodysplastic syndromes (MDS). Although heralded as a significant advancement, HMA lead to responses in less than half of patients and for those that respond most will relapse. As such, there is a crucial need to improve frontline therapy approaches. One promising strategy involves combining azacitidine or decitabine with investigational or existing therapies with the goal of achieving synergistic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 107 publications
(109 reference statements)
0
38
0
Order By: Relevance
“…Achieving this requires stronger collaboration and the advocacy of leading MDS investigators to help the pharmaceutical companies in designing more "pragmatic" clinical trial protocols with the goals of expanding access of trials to patients instead of just focusing on using the most stringent eligibility criteria to select the "Olympic athletes" of patients with MDS with the sole goal of achieving drug approval. 56 At the moment, the combination of antibody-drug conjugates (eg, anti-CD33 therapies), immune checkpoint inhibitors, and apoptosis-modulating agents such as the BCL-2 inhibitor venetoclax with HMA appear to be promising. Aside from a small number of pathologies such as chronic myeloid leukemia, in which long-term survival can be achieved with monotherapy, for most other tumors longterm survival (or cure) is only possible with combinationbased approaches.…”
Section: Many Patients Treated With Hma Monotherapy Do Not Derive Anymentioning
confidence: 99%
“…Achieving this requires stronger collaboration and the advocacy of leading MDS investigators to help the pharmaceutical companies in designing more "pragmatic" clinical trial protocols with the goals of expanding access of trials to patients instead of just focusing on using the most stringent eligibility criteria to select the "Olympic athletes" of patients with MDS with the sole goal of achieving drug approval. 56 At the moment, the combination of antibody-drug conjugates (eg, anti-CD33 therapies), immune checkpoint inhibitors, and apoptosis-modulating agents such as the BCL-2 inhibitor venetoclax with HMA appear to be promising. Aside from a small number of pathologies such as chronic myeloid leukemia, in which long-term survival can be achieved with monotherapy, for most other tumors longterm survival (or cure) is only possible with combinationbased approaches.…”
Section: Many Patients Treated With Hma Monotherapy Do Not Derive Anymentioning
confidence: 99%
“…However, several currently investigational drugs may represent a valid alternative in the future, for instance IDH inhibitors or new HMA such as SGI-110. Most of the current efforts are focused on optimizing treatment while using HMA as a backbone of combination therapy [16]. …”
Section: Alternatives In the Frontline And Relapse Settingsin Highmentioning
confidence: 99%
“…Efficacy of these combinations has not shown improvement over HMA monotherapy in initial treatment studies, and studies of this class on patients with HMA failure are limited [13]. Combination therapies with HMA are reviewed by Ball, et al [16]. In a phase 1 trial, 40 refractory higher risk MDS patients (nearly all after azacitidine failure) were treated with a cytarabine and vorinostat combination with an ORR of 15% [75].…”
Section: Alternatives In the Frontline And Relapse Settingsin Highmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleoside analogs based on epigenetic inhibitors 5-azacytidine and 5-aza-2′-dC are in Phase I-III clinical trials for many human diseases, and two DNMT inhibitors, azacytidine and decitabine, have shown efficacy and received FDA approval for the treatment of myelodysplastic syndrome but not solid tumors [31,32]. Nevertheless, some studies showed 5-aza-2′-dC decreased pancreatic cancer cell proliferation and induced cell cycle arrest in an in vitro model [33,34,35].…”
Section: Dna Methylationmentioning
confidence: 99%